The Kurdish quasi-state : development and dependency in post-Gulf War Iraq - Natali, Denise (Modern intellectual and political history of the Middle East., 2010)
Despite ongoing instability and underdevelopment in post -Saddam Iraq, some parts of the country have realized relative security and growth. The Kurdish north, once an isolated outpost for the Iraqi army and local militia, has become an internationally recognized autonomous region. In The Kurdish Quasi-State, Natali explains the Nature of this transformation and how it has influenced the relationship between the Kurdistan region and Iraq's central government. This much-needed scholarship focuses on foreign aid as helping to create and sustain the Kurdish quasi-state. It argues that the generous nature of external assistance to the Kurdishtan region over time has given it new forms of legitimacy and leverage in the country. Since 2003, the kurdistan region has gained representation in the central government and developed commercial investment and political ties with regional states and foreign governments. Drawing on extensive field research, Natali explores how this transition has had positive and unintended consequences on Kurdish-state relations. Greater complexity in the regional political economy has demanded new forms of compromise with the central government. The Kurdistan region may have become a distinct political entity that challenges Baghdad; however, the benefits of aid and the logic of quasi-statehood ensure that it will remain part of Iraq. Acutely familiar with the nuances of Kurdish politics, society, and culture, Natali has produced a timely and immensely important book for policy makers, scholars, and practitioners interested in the region. -- Book jacket.